2015
DOI: 10.3109/13668250.2015.1041466
|View full text |Cite
|
Sign up to set email alerts
|

Object control skills influence the physical activity of children with intellectual disability in a developing country: The Philippines

Abstract: Background Children with intellectual disability (ID) tend to have difficulties in reaching developmental milestones at predictable rates, including fundamental movement skills (FMS) proficiency. Low FMS proficiency tends to have a negative association with physical activity (PA) engagement. This study examined whether FMS components (locomotor, object control) influence PA levels in children with ID in the Philippines. Method The sample consisted of 60 children aged 5-14 years (M = 9.56, SD = 3.23) from speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 48 publications
(68 reference statements)
3
45
1
Order By: Relevance
“…In two studies with children (Eguia, Capio, & Simons, ; Westendorp et al, ), the relationships between physical activity level (daily step counts) or sport participation (Yes vs. No) and FMS dimensions were examined (Table ). As illustrated in Table , a significant relationship was found between physical activity (higher overall, weekday, and weekend daily step counts) or sport participation (those who participated had higher performance than those who did not participate) and object control skills in all the studies (Eguia et al, ; Westendorp et al, ). However, findings for the locomotor skills were mixed and inconclusive.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In two studies with children (Eguia, Capio, & Simons, ; Westendorp et al, ), the relationships between physical activity level (daily step counts) or sport participation (Yes vs. No) and FMS dimensions were examined (Table ). As illustrated in Table , a significant relationship was found between physical activity (higher overall, weekday, and weekend daily step counts) or sport participation (those who participated had higher performance than those who did not participate) and object control skills in all the studies (Eguia et al, ; Westendorp et al, ). However, findings for the locomotor skills were mixed and inconclusive.…”
Section: Resultsmentioning
confidence: 99%
“…However, findings for the locomotor skills were mixed and inconclusive. Indeed, Eguia et al () found a positive relationship between locomotor skills and overall and weekday physical activity and no relationship between locomotor skills and weekend physical activity. Additionally, Westendorp et al () found no significant relationship between locomotor skills and sport participation (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Object control skills impact health such that proficiency predicts cardiorespiratory fitness in adolescence among typically developing children [2]. Likewise, for children with intellectual disability, object control skills proficiency predicts sports participation [3] and habitual physical activity [4].…”
Section: Introductionmentioning
confidence: 99%
“…The TGMD-2 test is used in various contexts in the research, but the studies are mostly focused on searching for possibilities to influence gross motor skills (Bardid et al, 2013;Houwen, Hartman, Jonker, & Visscher, 2010). It can also be used in mentally handicapped people (Eguia, Capio, & Simons, 2015). The significance of the difference between the sub-tests (locomotor skills and object control skills) of children with mild mental disorder was evaluated by the t-test.…”
Section: Methodsmentioning
confidence: 99%